FROM A VICTIM OF THE FEMININE MYSTIQUE TO A HEROINE OF FEMINIST DECONSTRUCTION: REVISITING SELECTED POEMS OF SYLVIA PLATH - Mahdi, Maher A. (European Scientific Journal, ESJ, 2014)
Sylvia Plath’s poems mirror the ideological aspirations of its social context, and the construction of identity in her works falls under the impact of their specific contemporary historical context. The bulk of her aesthetic production reflects the ideologies of the Civil Rights Movement and its aim to elevate the cultural autonomy of American women. One of the major characteristics of this era roughly the 1960’s and 1970’s, is women’s endeavor to break out from the dominant patriarchal appropriation. This study purports to investigate some selected poems by Sylvia Plath and how these poems represented Plath as a relentless feminist writer and activist until her death. The study follows the development of the poet’s identity from a helpless object into a fighter who tried to win all her wars against the male sex. A large number of Plath’s poems deals with the feeling of women, treated as an object, a commodity, not allowed to be an independent person.